Nghiên cứu chế tạo màng niken hydroxit trên điện cực vàng bằng phương pháp điện hóa. - Sén, Trịnh Xuân; Hạnh, Trương Thị; Hà, Nguyễn Thị Cẩm (Vietnam Journal of Chemistry, 2012)
The nickel hydroxide/oxyhydroxide films on the gold substrate were formed by electrodeposition. The formation of the films on the gold electrode were studied by cyclic voltammetry between the potential range of 0.00 - 1.00 V (vs. SCE) in the solution consisting of Ni2+, complexion ligands and NaOH. These films were estimated by X-Ray diffraction (XRD) and Scaning Electron Microscopy (SEM). The oxidation electrochemical ability of ethanol on nickel hydroxide/oxyhydroxide thin film on the gold substrate were investigated.